Pengetahuan, Sikap dan Praktik Analis Kesehatan di Rumah Sakit X Provinsi Riau tentang Vaksinasi Hepatitis B - Huriatul Masdar; Sri Intan Agusmai; Rahmat Azhari Kemal; Fajri Marindra Siregar; Dedi Afandi (Jurnal Ilmu Kedokteran, 2022)
Hepatitis B is still one of public health problems in the world including in Indonesia. The most vulnerable group to hepatitis B virus exposure is healthcare workers including clinical laboratory technicians. The best way to prevent hepatitis B infection is by getting vaccination. Therefore clinical laboratory technicians are among prioritized subject in getting hepatitis B vaccination. However, hepatitis B vaccination for healthcare workers is not an obligation yet. The purpose of this study was to determine the knowledge, attitude and practice of hepatitis B vaccination among clinical laboratory technicians at X Hospital of Riau Province. This descriptive cross-sectional study was carried out between October 2021 and January 2022. Overall, 38 clinical laboratory technicians were recruited for this study. The Kolmogorov-Smirnov test is used to determine the relationship between knowledge with attitudes and practice. The results showed that 52.6% of respondents had good knowledge, 57.9% had a positive attitude and 68.4% had not been vaccinated against hepatitis B. Based on the results of bivariate analysis, there was no relationship between knowledge and attitude (p>0.05) or practice (p>0.05). Although more than 50% of respondents had good knowledge and attitude, the low number of clinical laboratory technicians in getting the hepatitis B vaccine remains a particular concern.